Arabica Coffee Business Development Strategy Analysis in Nagori Silimakuta Barat, Pamatang Silimahuta District, Simalungun Regency - Wahyunita Sitinjak; Arvita Netti Sihaloho; Alwi Fatra S Tanjung (Budapest International Research and Critics University, 2022)
The purpose of this study was to explain internal factors (strengths and weaknesses) and external factors (opportunities and threats) Arabica coffee farming and formulate a strategy for developing Arabica coffee farming in Nagori Silimakuta Barat, Pamatang Siimahuta District, Simalungun Regency. The analytical method used is descriptive analysis. Respondents were taken using purposive sampling method, namely as many as 30 farmers. Based on the results of the study, it can be concluded that Arabica coffee farming is located in Quadrant IV, namely the Turn Around Strategy is a very profitable situation. This farming business has opportunities and strengths so that they can take advantage of existing opportunities.